2011
DOI: 10.5902/198050982751
|View full text |Cite
|
Sign up to set email alerts
|

Conservação de sementes de marizeiro <i>Geoffroea spinosa</i> Jacq. utilizando diferentes embalagens e ambientes

Abstract: RESUMOO marizeiro (Geoffroea spinosa Jacq.) é uma espécie florestal importante, sobretudo por ser adaptada às condições de matas ciliares do semi-árido e ecossistemas associados, ocorrendo em vastas áreas do Nordeste brasileiro e no vale do rio São Francisco, sempre restrita a ambientes sazonalmente inundados. Este trabalho teve como objetivos avaliar o efeito de diferentes tipos de embalagens e do período de armazenamento sobre o processo germinativo e o vigor de sementes de Geoffroea spinosa Jacq. acondicion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…-Malphiguiaceae) from the 60 th storage day, packed in Kraft paper bag and under laboratory natural environment (27.2 ± 2 °C, 80% RH). In marizeiro seeds (Geoffroea spinosa Jacq -Fabaceae, Papolionoideae) kept in Kraft paper bag and stored in laboratory natural conditions (23.5 °C and 19.2 °C, 85% RH), rapid decrease in germination and vigor was observed from the 30 th storage day (SOUZA et al, 2011).…”
mentioning
confidence: 99%
“…-Malphiguiaceae) from the 60 th storage day, packed in Kraft paper bag and under laboratory natural environment (27.2 ± 2 °C, 80% RH). In marizeiro seeds (Geoffroea spinosa Jacq -Fabaceae, Papolionoideae) kept in Kraft paper bag and stored in laboratory natural conditions (23.5 °C and 19.2 °C, 85% RH), rapid decrease in germination and vigor was observed from the 30 th storage day (SOUZA et al, 2011).…”
mentioning
confidence: 99%
“…In contrast, Souza et al (2011), studying the storage of Geoffrea spinosa, a recalcitrant species from riparian forests (34.16% moisture), reported that cold storage and polyethylene packaging did not favor storage and, in the first three storage periods, there was a gradual decrease, followed by a slight increase in storage to ninety days.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, G. spinosa has occurrence restricted to certain habitats and may be vulnerable to extinction due to anthropic actions. However, remedial actions are hampered by the lack of data on the species (Souza et al, 2011).…”
Section: Discussionmentioning
confidence: 99%